THE JABALUL HIKMAH MODEL OF INTERDISCIPLINARY INTEGRATION - Moh. Roqib Moh. Roqib; Khafifatul Fian; Atabik Atabik; Nurfuadi Nurfuadi (LP2M IAI Al-Khairat Pamekasan, 2026)
This study analyzes the Jabalul Hikmah scientific integration model developed at UIN Prof. K. H. Saifuddin Zuhri Purwokerto as an effort to address the challenges of globalization and the Industrial Revolution 4.0. Using a qualitative approach and supported by questionnaire data from lecturers and students, this research examines the meaning, implementation, and implications of the integration model. The findings indicate that scientific integration is understood as an effort to unify various branches of knowledge in order to create a holistic understanding that connects spiritual, intellectual, and social aspects. Most respondents were familiar with the concept of Jabalul Hikmah, although their level of understanding varied. The implementation of integration is carried out through curriculum design, research, and community service, emphasizing interdisciplinary synergy. Metaphorically, the Jabalul Hikmah paradigm is symbolized by a mountain, representing wisdom, resilience, and the process of ascending toward perfection. This model emphasizes the integration of intellectuality, professionalism, and morality, so that graduates are expected to become insan kamil (the ideal human being). Thus, Jabalul Hikmah serves as a relevant and applicable integrative paradigm with the potential to strengthen the quality of Islamic higher education in facing complex global challenges.